Analysis of psychosocial factors associated with suicide mortality among the elderly in the state of Paraíba from 2009 to 2019 (Research, Society and Development, 2022)
Objective: To investigate the main psychosocial variables associated with the prevalence of suicide among the elderly in the 4 mesoregions of the state of Paraíba between 2009 and 2019. Methods: Epidemiological study with secondary data from the Mortality Information System from 2009 to 2019. Indicators of sex, ethnicity, age, schooling, marital status and place of occurrence of suicide victims were evaluated through descriptive statistics analysis with scatter plots boxplot. Results: There was a high incidence of suicides in the Sertão of Paraíba to the detriment of the other mesoregions, representing 35% of the total deaths in the state, as well as the presence of significant gaps in the process of producing death documents. Conclusion: The most recurrent sociodemographic profile was formed by brown and married men, up to 69 years old, with low education and who commit suicide at home.